High prevalence of the UGT1A1*28 variant in HIV-infected individuals in Greece - Panagopoulos, P; Paraskevis, D; Katsarolis, I; Sypsa, V; Detsika, M; Protopapas, K; Antoniadou, A; Papadopoulos, A.; Petrikkos, G; Hatzakis, A (Int J STD AIDSInt J STD AIDSInt J STD AIDS, 2014)
Hyperbilirubinaemia with or without jaundice is one of the side effects of atazanavir boosted with low-dose ritonavir (ATV/rit) related to the drug plasma levels, as a result of its metabolism by UGT1A1 - uridine diphosphate-glucuronosyl transferase. Genotyping for UGT1A1*28 before initiation of antiretroviral therapy containing atazanavir may aid in identifying individuals at risk of hyperbilirubinaemia. Our objective was to estimate the prevalence of the UGTA1A1*28 polymorphism in HIV-infected individuals in Greece and to determine its potential association with hyperbilirubinaemia in patients receiving ATV/rit. The prevalence of the UGTA1A1*28 variant was estimated in 79 HIV-infected patients prior to the administration of the first-line treatment. The UGTA1A1*28 variant was detected in 46 out of 79 individuals (58.2%). Antiretroviral therapy was administered to 64/79 patients (81%). Among them, 26/64 (40.6%) received ATV/rit. Of the ATV/rit-treated patients, 14 were found to be carriers of the UGT1A1*28 variant (54%), and maximum serum bilirubin levels were significantly higher in the carrier population (4.71 vs. 2.69 mg/dL, p = 0.026). In 50% of the population, maximum levels were recorded in the first month of follow-up. Although carriage of UGT1A1 is linked with the development of hyperbilirubinaemia, the implementation of a pharmacogenomic approach in clinical practice cannot yet be recommended as a standard of care.
Keywords: *Polymorphism, Genetic; Adult; Aged; Anti-HIV Agents/*administration & dosage/adverse effects; Antiretroviral Therapy, Highly Active; Atazanavir Sulfate; Bilirubin/metabolism; Cross-Sectional Studies; Glucuronosyltransferase/*genetics; Greece/epidemiology; HIV Infections/*drug therapy/epidemiology; HIV Protease Inhibitors/*administration & dosage/adverse effects; Humans; Hyperbilirubinemia/chemically induced/enzymology/*genetics; Middle Aged; Oligopeptides/*administration & dosage/adverse effects; Pharmacogenetics; Prevalence; Pyridines/*administration & dosage/adverse effects; Ritonavir/administration & dosage